2019
DOI: 10.35702/onc.10009
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of Biomarkers to Predict the Efficacy of Cancer Immunotherapy with Subcutaneous Low-Dose II-2 or with Immune Checkpoint Inhibitors

Abstract: The recent advances in the knowledge of the mechanisms involved in the antitumor immunity have allowed to elaborate immunotherapeutic strategies of cancer not only on the basis of an empiristic approach, as well as in the past years but on a better definition of the physiopathology of the anticancer immune response. In particular, it has been demonstrated that the antitumor immunity is mainly mediated by lymphocytes and that their functional status depends on the expression of specific cell-surface molecules, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The elaboration of possible association between CT and the more recent cancer immunotherapies with specific MABs against checkpoint inhibitor molecules, namely PD-1 and CTLA-4, which are responsible for the activation of T reg cells with a following suppression of the antitumor immune response, would have to be founded not only on the cytotoxic properties of CT against each specific tumor histotype, but also on the immune status of patients, namely their endogenous cytokine secretion, in an attempt to correct eventual alterations through the administration of chemotherapeutic agents provided by some specific effects on the cytokine network. In fact, it has been shown that the efficacy of cancer IT with anti-PD1 and anti-CTLA-4 MABs is depending on the biological response of patients, and that it is higher in the presence of an increase in LMR values under treatment, due to either lymphocyte increase, or monocyte decline, whereas no efficacy may be expected in the presence of an evident lymphocyte decline on therapy [27,28,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elaboration of possible association between CT and the more recent cancer immunotherapies with specific MABs against checkpoint inhibitor molecules, namely PD-1 and CTLA-4, which are responsible for the activation of T reg cells with a following suppression of the antitumor immune response, would have to be founded not only on the cytotoxic properties of CT against each specific tumor histotype, but also on the immune status of patients, namely their endogenous cytokine secretion, in an attempt to correct eventual alterations through the administration of chemotherapeutic agents provided by some specific effects on the cytokine network. In fact, it has been shown that the efficacy of cancer IT with anti-PD1 and anti-CTLA-4 MABs is depending on the biological response of patients, and that it is higher in the presence of an increase in LMR values under treatment, due to either lymphocyte increase, or monocyte decline, whereas no efficacy may be expected in the presence of an evident lymphocyte decline on therapy [27,28,50].…”
Section: Discussionmentioning
confidence: 99%
“…T reg cells may block the anticancer immunity through several mechanisms, which however have been substantially well clarified, and they are due to either a direct secretion of immunosuippressive molecules, namely TGF-beta itself, or a cell-cell contact after the expression on cell surface of particular molecules, the so-called checkpoint inhibitors, namely PD-1 with its twoligands, PD-L1 and PD-L2, and CTLA-4 [16,27,28]. Their block through the administration of specific monoclonal antibodies (MABs) has appeared to allow an effective anticancer immune reaction and a control of the neoplastic growth.…”
Section: The Physiology Of Regulatory T Lymphocytesmentioning
confidence: 99%